Bacteria and Archaea Synergistically Convert Glycine Betaine to Biogenic Methane in the Formosa Cold Seep of the South China Sea - Lingyan Li; Wenting Zhang; Shengjie Zhang; Lei Song; Qinglei Sun; Huan Zhang; Hua Xiang; Xiuzhu Dong (mSystems, 2021)
ABSTRACT Cold seeps are globally widespread seafloor ecosystems that feature abundant methane production and flourishing chemotrophic benthic communities. Chemical evidence indicates that cold seep methane is largely biogenic; however, the primary methane-producing organisms and associated pathways involved in methanogenesis remain elusive. This work detected methane production when glycine betaine (GBT) or trimethylamine (TMA) was added to the sediment microcosms of the Formosa cold seep, South China Sea. The methane production was suppressed by antibiotic inhibition of bacteria, while GBT was accumulated. This suggests that the widely used osmoprotectant GBT could be converted to cold seep biogenic methane via the synergistic activity of bacteria and methanogenic archaea because archaea are not sensitive to antibiotics and no bacteria are known to produce ample methane (mM). 16S rRNA gene diversity analyses revealed that the predominant bacterial and archaeal genera in the GBT-amended methanogenic microcosms included Oceanirhabdus and Methanococcoides. Moreover, metagenomic analyses detected the presence of grdH and mtgB genes that are involved in GBT reduction and demethylation, respectively. Two novel species were obtained, including bacterium Oceanirhabdus seepicola, which reduces GBT to TMA, and a methanogenic archaeon, Methanococcoides seepicolus, which produces methane from TMA and GBT. The two strains reconstituted coculture efficiently converted GBT to methane at 18°C; however, at 4°C addition of dimethylglycine (DMG), the GBT demethylation product, was necessary. Therefore, this work demonstrated that GBT is the precursor not only of the biogenic methane but also of the cryoprotectant DMG to the microorganisms at the Formosa cold seep. IMPORTANCE Numerous cold seeps have been found in global continental margins where methane is enriched in pore waters that are forced upward from sediments. Therefore, high concerns have been focused on the methane-producing organisms and the metabolic pathways in these environments because methane is a potent greenhouse gas. In this study, GBT was identified as the main precursor for methane in the Formosa cold seep of the South China Sea. Further, synergism of bacteria and methanogenic archaea was identified in GBT conversion to methane via the GBT reduction pathway, while methanogen-mediated GBT demethylation to methane was also observed. In addition, GBT-demethylated product dimethyl glycine acted as a cryoprotectant that promoted the cold seep microorganisms at cold temperatures. GBT is an osmoprotectant that is widely used by marine organisms, and therefore, the GBT-derived methanogenic pathway reported here could be widely distributed among global cold seep environments.